Variety in fruit and vegetable consumption and the risk of lung cancer in the European prospective investigation into cancer and nutrition. - Büchner, F; Bueno-de-Mesquita, H; Ros, M; Overvad, K; Dahm, C; Hansen, L; Tjønneland, A; Clavel-Chapelon, F; Boutron-Ruault, M; Touillaud, M; Kaaks, R; Rohrmann, S; et al. (2010)
BACKGROUND: We investigated whether a varied consumption of vegetables and fruits is associated with lower lung cancer risk in the European Prospective Investigation into Cancer and Nutrition study. METHODS: After a mean follow-up of 8.7 years, 1,613 of 452,187 participants with complete information were diagnosed with lung cancer. Diet diversity scores (DDS) were used to quantify the variety in fruit and vegetable consumption. Multivariable proportional hazards models were used to assess the associations between DDS and lung cancer risk. All models were adjusted for smoking behavior and the total consumption of fruit and vegetables. RESULTS: With increasing variety in vegetable subgroups, risk of lung cancer decreases [hazard ratios (HR), 0.77; 95% confidence interval (CI), 0.64-0.94 highest versus lowest quartile; P trend = 0.02]. This inverse association is restricted to current smokers (HR, 0.73; 95% CI, 0.57-0.93 highest versus lowest quartile; P trend = 0.03). In continuous analyses, in current smokers, lower risks were observed for squamous cell carcinomas with more variety in fruit and vegetable products combined (HR/two products, 0.88; 95% CI, 0.82-0.95), vegetable subgroups (HR/subgroup, 0.88; 95% CI, 0.79-0.97), vegetable products (HR/two products, 0.87; 95% CI, 0.79-0.96), and fruit products (HR/two products, 0.84; 95% CI, 0.72-0.97). CONCLUSION: Variety in vegetable consumption was inversely associated with lung cancer risk among current smokers. Risk of squamous cell carcinomas was reduced with increasing variety in fruit and/or vegetable consumption, which was mainly driven by the effect in current smokers. IMPACT: Independent from quantity of consumption, variety in fruit and vegetable consumption may decrease lung cancer risk.